Вечный огонь: повести, очерки / О. И. Курганов - Курганов Оскар Иеремеевич (Современник, 1985)
Экземпляры: ф.11 (20170310) / Инвентарный номер: 020556 / Цена: 1.00 / Авт.знак: К 93 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6